Metformin, Rapamycin, or Nicotinamide Mononucleotide Pretreatment Attenuate Cognitive Impairment After Cerebral Hypoperfusion by Inhibiting Microglial Phagocytosis - Yu, Mengdi; Zheng, Xiaoying; Cheng, Fangyu; Shao, Bei; Zhuge, Qichuan; Jin, Kunlin (Frontiers in Neurology, 2022)
Vascular cognitive impairment (VCI) is the second leading form of dementia after Alzheimer's disease (AD) plaguing the elder population. Despite the enormous prevalence of VCI, the biological basis of this disease has been much less well-studied than that of AD, with no specific therapy currently existing to prevent or treat VCI. As VCI mainly occurs in the elderly, the role of anti-aging drugs including metformin, rapamycin, and nicotinamide mono nucleotide (NMN), and the underlying mechanism remain uncertain. Here, we examined the role of metformin, rapamycin, and NMN in cognitive function, white matter integrity, microglial response, and phagocytosis in a rat model of VCI by bilateral common carotid artery occlusion (BCCAO). BCCAO-induced chronic cerebral hypoperfusion could cause spatial working memory deficits and white matter lesions (WMLs), along with increasing microglial activation and phagocytosis compared to sham-operated rats. We found the cognitive impairment was significantly improved in BCCAO rats pretreated with these three drugs for 14 days before BCCAO compared with the vehicle group by the analysis of the Morris water maze and new object recognition tests. Pretreatment of metformin, rapamycin, or NMN also increased myelin basic protein (MBP, a marker for myelin) expression and reduced SMI32 (a marker for demyelinated axons) intensity and SMI32/MBP ratio compared with the vehicle group, suggesting that these drugs could ameliorate BCCAO-induced WMLs. The findings were confirmed by Luxol fast blue (LFB) stain, which is designed for staining myelin/myelinated axons. We further found that pretreatment of metformin, rapamycin, or NMN reduced microglial activation and the number of M1 microglia, but increased the number of M2 microglia compared to the vehicle group. Importantly, the number of MBP+/Iba1+/CD68+ microglia was significantly reduced in the BCCAO rats pretreated with these three drugs compared with the vehicle group, suggesting that these drugs suppress microglial phagocytosis. No significant difference was found between the groups pretreated with metformin, rapamycin, or NMN. Our data suggest that metformin, rapamycin, or NMN could protect or attenuate cognitive impairment and WMLs by modifying microglial polarization and inhibiting phagocytosis. The findings may open a new avenue for VCI treatment.